Compliance to Evidence-Based Dietary Management Practices for COVID-19 by Pakistani Dietitians - Maira Tanveer; Izma Azhar; Mahnoor Maqsood; Nafeesa Ismail; Rabia Sagheer; Umar Bacha; Afifa Tanweer (BioScientific Review, 2026)
Aim. This study aims to examine the role of evidence-based dietary recommendations practiced by dietitians in clinical settings for COVID-19.Methods. Secondary data was collected by gathering evidence-based literature from credible organizations and literature sources regarding dietary guidelines on the management of COVID-19. Quantitative data were collected through a questionnaire comprising 20 general questions and filled by 62 participants (4 males and 58 females). The questionnaire was designed to examine the recommended dietary practices. Descriptive statistics were used to determine the alignment of dietitians’ knowledge and practices with the literature. Results. Although there is a need to improve the approaches and gain more evidence-based knowledge, it is satisfactory to know that dietary guidelines and approaches provided by practicing dietitians or nutritionists in local clinical settings in Pakistan are based on evidence.Conclusion. The study emphasizes the importance of integrating validated dietary guidelines into clinical nutritional practice for both preventive and therapeutic care. Future research should focus on assessing the long-term effectiveness of these dietary interventions and exploring gaps in their consistent implementation across diverse clinical settings.